The Impact of STEM Applications on Problem-Solving Skills of 4th-Grade Students - Raşit Zengin; Tuğçe Kavak; Gonca Keçeci; Fikriye Kırbağ Zengin (Journal of Science Learning, 2022)
This study examined the impact of STEM applications realized with 4th-grade elementary school students on their problem-solving skills. The study was conducted within the convergent parallel design framework, a mixed research method. The research was carried out with 42 4th-grade primary school students, 21 in the experimental group and 21 in the control group, studying in a public school in Turkey. In the study, which lasted for ten weeks, STEM applications were carried out with the students in the experimental group. The control group applied the current science curriculum without performing STEM applications. The research data consists of the Developing Problem Solving Inventory for Children at the Level of Primary Education (PSIC) and the semi-structured interview conducted with the students in the experimental group. Quantitative data were analyzed using an independent sample t-test, while qualitative data were analyzed with content analysis. When the PSIC post-test scores of the 4th-grade primary school students in the experimental and control groups were examined, a statistically significant difference was found in favor of the experimental group. According to the qualitative data analysis of the study, it was determined that the students encountered various problems in the process and developed solutions for them. The students stated that using STEM activities in the classes is fun, so they learn more permanently and easily, and they want the classes to be delivered in this way from now on.